Cost-Effective Analysis of a Mobile Dental Van in Delivering Primary Oral Health Care among Adopted Schools of a Dental College, Bangalore-a Retrospective Study - Khechari A Chavan; Radha G; Rekha R (Shiraz University of Medical Sciences, 2021)
Background: Oral diseases remain one of the major public health challenges in India. Mobile dental services may be used as alternatives to supplement the standard care in order to reach underserved populations in several countries. However, not enough research has been conducted on school children. Hence, this paper aimed to evaluate the cost-effectiveness (where cost is expressed in monetary units and results in non-monetary units) of a mobile dental vehicle (MDV) in delivering primary oral health care among adopted schools of a dental college in Bengaluru. Methods: This retrospective population-based study was conducted among adopted children of the age group of 4-15 years in Bengaluru. The data were collected from the college camp out-patient register over three academic years of 2017-18, 2018-19, and 2019-20 in December 2020. Cost-effectiveness was calculated utilizing the formula total cost (direct+indirect) of service provision with the total number of the patients who used the services in the same period. Statistical tests unpaired student t-test, ANOVA, Tukey's post hoc test, and all the statistical tests were set with a level of significance (p <0.1), which was conducted using the statistical package SPSS version 19.0. Results: A total of 14,806 patients and 75,421 teeth were treated in mobile dental vehicle. The cost for each patient was around 259.0/- rupees and for each tooth, around 51.3/-rupees. Around 2686 teeth were benefitted from the use of a portable dental chair. Therefore, the cost of treating each tooth was around 12.3/- rupees. The mean difference in the number of the treated patients was found to be significantly decreasing. Conclusion: We conducted the current study to demonstrate the costs of providing primary oral health care among adopted schools. Mobile dental vehicle and the portable dental chair were found to be cost-effective in delivering primary oral health care.